Room temperature chiral smectic C liquid crystal bearing para-phenylchclohexyl mesogenic core - Kim, Doo Hun; Goh, Munju (IOP Publishing Ltd., 2020)
Novel calamitic chiral liquid crystal (LC) was synthesized by introducing chiral butanol moiety into the para-phenylcyclohexyl mesogenic core. We confirmed the liquid crystallinity of chiral LC using DSC, POM and XRD measurements. The chiral LC shows a stable enantiomeric LC phase both cooling and heating procedure. It was found that the chiral LC exhibits a stable LC phase at room temperature. In addition, the chiral LC was assigned as chiral smectic C (Sc*) phase with a tilted angle of 22.7 degrees.